2022
DOI: 10.3390/antibiotics11030374
|View full text |Cite
|
Sign up to set email alerts
|

A One Health Approach Molecular Analysis of Staphylococcus aureus Reveals Distinct Lineages in Isolates from Miranda Donkeys (Equus asinus) and Their Handlers

Abstract: Donkeys (Equus asinus) are in decline in Europe. Occupational exposure to farm animals has been associated with increased staphylococci carriage. We aimed to isolate S. aureus and coagulase-negative staphylococci (CoNS) from donkeys and handlers and characterize the antimicrobial resistance profiles and genetic lineages of S. aureus strains. Oral and nasal swab samples were collected from 49 Miranda donkeys and 23 handlers from 15 different farms. Staphylococci species were identified by MALDI-TOF MS. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Nevertheless, compared to the present results, studies by other authors have shown a higher percentage of strains resistant to this antibiotic (22.4% and 44%) [ 41 , 52 ]. The erm genes confer cross-resistance to macrolides, lincosamides, and streptogramins B [ 53 ]. Antimicrobial resistance results obtained in this study correlate with antibiotics that are used to treat cattle infections in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, compared to the present results, studies by other authors have shown a higher percentage of strains resistant to this antibiotic (22.4% and 44%) [ 41 , 52 ]. The erm genes confer cross-resistance to macrolides, lincosamides, and streptogramins B [ 53 ]. Antimicrobial resistance results obtained in this study correlate with antibiotics that are used to treat cattle infections in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this work was a retrospective study that included 214 S. aureus strains, comprising mec A-MRSA, mec C-MRSA, and methicillin-susceptible S. aureus (MSSA) isolates. The isolates were recovered from animals’ infections and from healthy animals between 2018 and 2021: purulent lesions of pigs ( n = 43), purulent lesions of farm rabbits ( n = 16), healthy cattle ( n = 36), quails ( n = 29), hunting dogs ( n = 11), camels ( n = 11), Miranda donkeys ( n = 4), wild hares ( n = 3), wild rodents ( n = 38) and wild owls ( n = 23) [ 6 , 7 , 8 , 12 , 40 , 41 , 42 ]. All isolates were previously characterized regarding their antimicrobial resistance and genetic lineages by MLST, spa -and agr -typing which will be used to performed statistical analysis to study the correlations between biofilm formation (evaluated in this study) and antimicrobial resistance and genetic lineages of the isolates [ 6 , 7 , 8 , 12 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the prevalence of S. aureus in chickens, pigs and sheep can be up to 90%, 42% and 29%, respectively, and in cows it ranges from 14 and 35% [ 5 ]. S. aureus has been detected in a taxonomically diverse range of animals, such as, carnivores, ruminants, lagomorphs, insectivore, reptiles and birds, living in a wide range of ecological niches [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Nevertheless, as in humans, S. aureus can also cause various types of infections in animals, the most common of which are mastitis in bovine, skin and soft tissue infections in companion animals, septic arthritis in poultry, abscesses in rabbits among others [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This lineage is primarily associated with humans, but it has been also found among animals and in the environment [ 55 , 62 ]. Moreover, ST30-MSSA-t012 has been detected in hospitalized humans and livestock workers in Portugal, in the same region where the samples of this study were collected [ 63 , 64 ]. Both ST30-MSSA-t012 isolates carried the virulence gene tst , in addition to the hemolysins genes, which is in accordance with other studies that have shown that S. aureus ST30 often carries pathogenicity islands including the tst gene [ 65 ].…”
Section: Discussionmentioning
confidence: 99%